Features of immunity by various constellations of principal adaptation hormones and autonomous regulation in practically healthy people - Anatoliy I Gozhenko (Journal of Education, Health and Sport, 2016)
Gozhenko Anatoliy I, Hrytsak Yaroslav L, Barylyak Liliya G, Kovbasnyuk Marta M, Tkachuk Svitlana P, Korolyshyn Tetyana A, Matiyishyn Galyna Yo, Zukow Walery, Popovych Igor L. Features of immunity by various constellations of principal adaptation hormones and autonomous regulation in practically healthy people. Journal of Education, Health and Sport. 2016;6(10):215-235. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.160979